Therapeutic applications of bone marrow-derived stem cells in ischemic stroke. (June 2013) - Wang, Liuqing; Lin, Zhenzhen; Shao, Bei; Zhuge, Qichuan; Jin, Kunlin
Abstract : The treatment of ischemic stroke remains a daunting task as few therapeutic strategies have proven effective. Systemic thrombolysis with intravenous tissue plasminogen activator (tPA) remains the only proven treatment to improve clinical outcome of patients with acute ischemic stroke. But because of increased risk of hemorrhage beyond 4·5 hours post-stroke, few stroke patients (1–2%) benefit from tPA. Therefore, new therapies need to be found that protect and repair the damaged brain after stroke. The discovery of stem cells holds great promise for the cure of many diseases, including stroke. The bone marrow-derived stem cells (BMSCs) have particularly gained a great deal of attention, as BMSCs can differentiate into different lineages under specific conditions. In addition, obtaining marrow cells would be easy and using patient's own BMSCs may eliminate the risk of rejection. Therapeutic effects have been reported in animal models of stroke after transplantation of BMSCs. Initial clinical trials using BMSC transplantation have been performed in patients with ischemic stroke. Additional trials are evaluating the impact of BMSCs on safety, feasibility, and efficacy for stroke treatment. However, more information about the appropriate cell type, timing of administration, cell delivery route, and optimal dose for translational applications remains largely unexplored. This article reviews the recent progress and future perspectives in BMSC-based therapy for ischemic stroke, focusing on cell delivery route and time window of cell transplantation for treatment of ischemic stroke in animal models and clinical trials.